Microscopia de força atômica na análise de rugosidade e da dimensão fractal de membranas celulares - Silva, Givanildo Rodrigues da (2016)
A multi-probe scanning microscopy system was used to study the morphological properties of cells. Initially, an atomic force microscope was used to characterize and map the surface of the cell membrane of macrophages. In the present work we investigated the behavior of murine macrophages in different situations and observed some of the parameters that are capable of assigning quantitative value, the alterations suffered by the cell membrane. Cells were adhered to fibronectin films, and also treated with cytochalasin D, to compare with untreated samples and adhered only to glass. With this procedure it is possible to quantify the interference of the cellular adhesion to an extracellular matrix, through the parameters of roughness (mean roughness and quadratic mean roughness) and fractal dimension. The results of these studies show that cytoskeletal interactions between the cell and the extracellular matrix can directly affect cell membrane morphology by modifying the cellular cytoskeletal physical properties. In particular, we analyzed the roughness parameters and fractal dimension of cells, which are important quantifiers of possible changes in the cell membrane structure. Finally, we noticed that the technique of atomic force microscopy is extremely useful for the morphological characterization of biological samples, that the adhesion of the cell to the extracellular matrix interferes in the changes in the cell morphology and that in our samples the roughness was a parameter more to quantify these changes than the fractal dimension.